Cyber resilience conceptual model for European Union NIS2 standards implementation in Slovakia - Jozef Ristvej; Michal Tonhauser; Daniel Chovanec; Jozef Kubás; Boris Kollár; Zenon Zamiar (Scientific Reports)
Abstract The use of modern information and communication technologies in the business environment, as well as in everyday life has become common. However, with the dynamic development of these technologies, the risk of their abuse is also increasing. In this context, cyber resilience is coming into focus. This paper discusses the development of a Cyber Resilience Model based on the implementation of the normative acts of cyber security and the NIS2 directive in the context of crisis management. The model has the ambition to increase the level of cyber resilience. Its creation has been tailored for application in the structures of the Slovak Republic. The paper also deals with the definition of cyber resilience, as the term has not received sufficient attention and there are many different definitions. The findings of this paper have the potential to be applied in other countries of the European Union too, as the principles of cyber security and the obligation to implement legislation apply to all EU countries.